Toward a resource poetics in Muriel Rukeyser's Book of the Dead and Mark Nowak's Coal Mountain Elementary. Issue 3 (4th March 2021) - Parks, Justin
ABSTRACT: Muriel Rukeyser's 1936 documentary poem The Book of the Dead appropriates various forms of textual evidence to document a devastating mining disaster that occurred in 1930 in rural Gauley Bridge, West Virginia. Written in the aftermath of the post-2008 financial crisis, Mark Nowak's 2009 text Coal Mountain Elementary revisits the same landscape Rukeyser had sought out seventy years earlier, and makes use of a similar technique as it combines reports of a 2006 mine explosion in Sago, West Virginia, with news reports from Chinese mining accidents and other materials. Both poems dramatise the distance separating extractivism-vulnerable landscapes of the periphery (rural, or in Nowak's case, global) from the accumulation of profits in the core. In reading these two texts side-by-side, it becomes clear that beyond their thematic similarities, the two poems also engage and adapt a methodology I call 'resource poetics', in which extractivist practices are exposed to view through poems' material incorporation of textual artefacts testifying to their ruinous effects. As such, the two poems, situated roughly seventy-five years apart, offer trenchant critiques of modernity in its extractivist mode.